The Degree of Application of TQM System in Basic Education Schools Afield study in AL -Hassakeh Schools)) (Damascus University Journal of educational and Psychologyical sciences, 2021)
The research aimed at Measuring the applicability of TQM system in basic education schools from the viewpoint of teachers in AL-Hassakeh Schools according to (gender, academic qualification, and years of experience). To achieve the objectives of the research, the researcher selected a sample of teachers in basic education schools reached (277) teachers and used a questionnaire which included (43) items with (5) domains according to the three-graded measure.The research finished to: The extent of basic education schools managers' application of  the total quality management TQM system from the viewpoint of teachers was medium. In addition, there were statistically significant differences at the level of (a ≤0.05) between the averages of sample's individual answers concerning the extent of applying the total quality management TQM system according to the academic qualification, and years of experience, but there were no statistically significant differences according to the gender.  In light of the study some suggestions were provided that can circulated to implement TQM in basic education schools.
Keywords: : Basic Education Schools; Quality; Total Quality Management System.